AFRICA’S WEB CONTENT: CURRENT STATUS - Stephen M., Mutula (Malaysian Journal of Library and Information Science, 2002)
This paper addresses the subject of Africa content online, looking at the current status of Africa’s Internet infrastructure and Web presence. The paper assesses the forms of content available and provides benchmarking criteria for quality. Comparative statistics of Africa’s Web content with other regions of the world are given based on e-government indices. This paper assumes that e-government indices defined as the mean figures derived from variables such as the web presence, telecommunication infrastructure and human capital measures can provide fairly accurate measure of web content of any country. The paper provides strategies to stimulate online content creation in Africa. Current developments within Africa that have some bearing on local content creation are discussed. Finally the paper discusses challenges in local content creation in Africa and makes suggestions for the way forward. Throughout this paper, Africa Web content is taken to refer to content generated in Africa and mounted on the Web or any other global networks and accessed either remotely or locally.